The nuclear migration signal of Xenopus laevis nucleoplasmin. - Bürglin, T R (1987)
Nucleoplasmin is the most abundant protein in the nucleus of Xenopus laevis oocytes. Its ability to target to the nucleus when microinjected into the cytoplasm has been the subject of many studies central to our understanding of how proteins segregate into nuclei. Using a cDNA clone we constructed beta-galactosidase-nucleoplasmin hybrids in modified bacterial expression vectors. The fusion proteins were expressed in Escherichia coli, purified and injected into the cytoplasm of X. laevis oocytes. The distribution of the fusion proteins between the cytoplasmic and nuclear compartments were analysed after incubation of various lengths of time. The results show that the signal sequence for nuclear transport is located close to the carboxy terminus of the protein. The signal sequence has been mapped to a small stretch of amino acids, containing a stretch of four lysines analogous to the SV40 large-T antigen signal.